Enhanced Photocatalytic Degradation of Acid Orange 7 by AgBr/BiVO4 under Visible Light (Journal of Fiber Bioengineering and Informatics, 2018)
Recently, the use of co-catalysts has been an important alternative method to improve the visiblelight photocatalytic activity of pure semiconductor materials. A novel photocatalyst AgBr/BiVO4 wasprepared by hydrothermal synthesis and chemical deposition method. The degradation of acid orange7 was enhanced by AgBr/BiVO4 than pure BiVO4, which was eliminated 92.96% within 80 min undervisible light irradiation. It was found that the doping of AgBr could greatly improve the photocatalyticactivity of BiVO4 by reducing the recombination of electrons and holes. Prepared photocatalystswere characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), UV-vis diffusereflectance spectra techniques (UV-vis) and X-ray photoelectron spectroscopy (XPS).